Role of mastitis in on-farm deaths of Finnish dairy cows - Hagner, K.A.; Nordgren, Heli S.; Sarjokari, K.; Sukura, A.; Rajala-Schultz, P.J. (Elsevier, 2024)
According to our recent necropsy-based study, mastitis is the most common underlying diagnosis of on-farm deaths in Finnish dairy cows. However, it remained unanswered to what extent mastitis has contributed to death of all necropsied cows. In the present study, based on histopathology, we detected one-third of the necropsied dairy cows having active inflammatory udder lesions (n = 110). The role of mastitis varied and was interpreted by causes of death (underlying, intermediate, immediate, other significant). Mastitis was most commonly the underlying (28%) or both immediate and underlying cause of death (48%), and only seldom was it the immediate (4%) or intermediate (4%) cause of death. Mastitis occurred either as the only cause leading to death (mastitis only, MO; 39%), or with many other contributing diseases (multiple diseases, MD; 61%), which were interacting with mastitis and together leading to death. Between these groups (MO vs. MD), time of mastitis occurrence during lactation, producer-reported duration of illness, clinical signs, and medication differed, as well the histopathologic severity of mastitis. The cases where mastitis was the only initial insult occurred evenly throughout the entire lactation, but the cases with many interacting diseases were clustered in early lactation. In MD cows, cases of mastitis occurred concurrently with metritis (31%), aspiration pneumonia (24%), acute trauma or dystocia (15%), or with other diseases, such as ketosis, hepatic lipidosis, rumenitis, and abomasal diseases. For a pathologist, the gross mastitis diagnosis was most challenging at the beginning of the lactation, especially if inflammation was mild to moderate, suggesting the value of histopathologic examination being highest at that time. Also, producers reported mastitis signs less frequently if cow had many simultaneously occurring diseases. Therefore, even if clinical signs of other diseases are present, the udder should be considered a potential cause of illness and should be examined, especially in dry and transition-period cows.
Keywords: dairy cow; mastitis; on-farm death; necropsy; histopathology